Customer relationship management in a tertiary level hospital - Bilkis, Afsana; Miah, Khorshed Ali; Sultana, Arifa; Parvin, Mst Shahida; Mittra, China Rani; Saha, Ashees Kumar (Asian Journal of Medical and Biological Research, 2020)
This cross-sectional study was conducted at OPD of Khulna Medical College Hospital (KMCH). This study aimed to assess the status of Customer Relationship Management (CRM) in a tertiary level hospital in Khulna city from 1st January to 31st December 2016. Total 200 samples were included purposively. Among them 150 respondents were health care receivers and 50 participants were health care providers and interviewed with a pre-tested semi-structured questionnaire and a checklist was used to collect information regarding administrative facility, physical facility and utility services. Data were analyzed by using Statistical Package for Social Science version (SPSS) 22 and appropriate statistical tests were performed. Most (62.3%) of the service receivers were satisfied about the doctors dealing in OPD. It was found that majority of service provider (82%) had not knowledge about CRM and its objectives. Majority (82%) of the service receiver came to hospital willingly and (47.3%) of service receivers were spent less than one hours for getting total treatment.). Most (40%) of service providers said that there were a lack of service provider, modern equipment and medication in the OPD and they recommended that enhanced manpower, modern equipment and adequate supply of medication. About half 49.3% of the service receivers suggested in manpower should be increased. Therefore, attempts could be taken to implement customer relationship management as a process for improving hospitals performance and improving communication between service providers and service receiver in hospitals. Asian J. Med. Biol. Res. September 2020, 6(3): 599-607